(untitled) (Research, Society and Development, 2021)
To relate social isolation in the elderly and mortality, and its effects, psychic, emotional and social, in the elderly, caused by the pandemic of COVID-19. Research conducted as a Bibliographic Literature Review by the integrative review method, which summarizes theoretical literature to provide broad understanding about a given phenomenon. The PICo strategy, was used to construct research questions. The most vulnerable population group, with the highest lethality in relation to COVID-19, is the elderly. This fact is due to immunosenescence, which increases vulnerability to infectious diseases and brings the worst prognosis for those with chronic non-communicable diseases. However, the human being is not only biophysical, but also psychosociocultural. It is up to health professionals to suggest measures to contain the damage to the health of the elderly, as strategies for guidance on social isolation to avoid contamination, therefore, need specific knowledge about this population, aimed not only to combat COVID-19, as well as other health problems affecting this population.